A Social Return on Investment evaluation of the Emotion-Mind Dynamic (EMD) two phase social prescribing life coaching intervention to support mental health and wellbeing. (2022) - Makanjuola, Abraham; Lynch, Mary; Hartfiel, Ned; Cuthbert, Andrew; Winrow, Eira; Edwards, Rhiannon Tudor
No abstract available